(untitled) (Selecciones Matemáticas, 2022)
In this paper we prove a result on 0-cycles on surfaces as an application of the theorem on the kernel of the Gysin homomorphism of Chow groups of 0-cycles of degree zero induced by the embedding of a curve into a surface, and we study the connection of this result with Bloch’s conjecture and constant cycles curves.